Cytokinins in the Bryophyte Physcomitrella patens: Analyses of Activity, Distribution, and Cytokinin Oxidase/Dehydrogenase Overexpression Reveal the Role of Extracellular Cytokinins - von Schwartzenberg, Klaus (American Society of Plant Biologists, 2007)
Ultra-performance liquid chromatography-tandem mass spectrometry was used to establish the cytokinin profile of the bryophyte Physcomitrella patens (Hedw.) B.S.G.; of 40 analyzed cytokinins, 20 were detected. cis-Zeatin-riboside-O-glucoside, N(6)-(Δ(2)-isopentenyl)adenosine-5′-monophosphate (iPRMP), and trans-zeatin-riboside-O-glucoside were the most abundant intracellular cytokinins. In addition, the aromatic cytokinins N(6)-benzyladenosine (BAR), N(6)-benzyladenine, meta-, and ortho-topolin were detected. Unexpectedly, the most abundant extracellular cytokinin was the nucleotide iPRMP, and its identity was confirmed by quadrupole time-of-flight mass spectrometry. The effects of overexpressing a heterologous cytokinin oxidase/dehydrogenase (CKX; EC 1.4.3.18/1.5.99.12) gene (AtCKX2 from Arabidopsis [Arabidopsis thaliana]) on the intracellular and extracellular distribution of cytokinins was assessed. In cultures of CKX-transformed plants, ultra-performance liquid chromatography-tandem mass spectrometry measurements showed that there were pronounced reductions in the extracellular concentrations of N(6)-(Δ(2)-isopentenyl)adenine (iP) and N(6)-(Δ(2)-isopentenyl)adenosine (iPR), but their intracellular cytokinin concentrations were only slightly affected. In vitro and in vivo measured CKX activity was shown to be strongly increased in the transformants. Major phenotypic changes observed in the CKX-overexpressing plants included reduced and retarded budding, absence of sexual reproduction, and abnormal protonema cells. In bud-induction bioassays with wild-type Physcomitrella, the nucleotides iPRMP, trans-zeatin-riboside-5′-monophosphate, BAR monophosphate, and the cis-zeatin forms cZ and cZR had no detectable effects, while the activities displayed by other selected cytokinins were in the following order: iP > tZ > N(6)-benzyladenine > BAR > iPR > tZR > meta-topolin > dihydrozeatin > ortho-topolin. The results on wild type and CKX transgenics suggest that extracellular iP and iPR are the main cytokinins responsible for inducing buds in the bryophyte Physcomitrella. Cytokinin profile is discussed regarding the evolution of cytokinin biosynthetic pathways.